Analysis of The Use and Maintenance of Mooring Ropes To Support Safety When Ships Are Moored - Adam Fawwaz Alan Santoso; Anugrah Nur Prasetyo; Muhammad Dahri; Firdaus Sitepu (International Journal of Science and Environment (IJSE), 2026)
This research is motivated by the high risk of accidents in ship berthing operations due to mooring line failures that still frequently occur in ports. The purpose of this study is to analyze the use and maintenance of mooring lines in supporting ship safety when berthing. This study uses a descriptive qualitative approach. The study population is all crew members involved in mooring and unmooring activities on the Mv. Tanto Sentosa, while the sample was selected using a purposive sampling technique based on direct involvement in berthing operations. The research instrument is the researcher himself, with data collection techniques through observation, interviews, and documentation. Data analysis was carried out using the interactive model of Miles, Huberman, and Saldaña through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the use of mooring lines is in accordance with the function and Ocimf Meg3/Meg4 standards, and the equipment is in good condition based on CCS inspections. Maintenance is carried out routinely through rinsing, storage, and periodic inspections. However, weaknesses are still found in the documentation aspect, namely the absence of a Line Management Plan (LMP). The conclusion of this study shows that the use and maintenance of mooring lines has been running well and supports ship safety, but improvements are needed in the maintenance documentation system to comply with IMO standards.